2010
DOI: 10.1177/1043454209358411
|View full text |Cite
|
Sign up to set email alerts
|

Families of Young Pediatric Cancer Survivors: A Cross-Sectional Survey Examining Physical Activity Behavior and Health-Related Quality of Life

Abstract: The present study examined physical activity levels within young families of pediatric cancer survivors and the relationship between physical activity and health-related quality of life (HRQL). Nineteen families were recruited, including 33 parents, 17 pediatric cancer survivors, and 10 siblings. Families completed a self-report survey on background information, physical activity levels, and PedsQL generic core scale for child HRQL. Results of this cross-sectional study indicate that families were generally ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
44
0
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 73 publications
(89 reference statements)
3
44
0
1
Order By: Relevance
“…As children grow older, this relation becomes less consistent (Gustafson & Rhodes, 2006; Heitzler et al, 2006; Sallis et al, 2000), with the influence of parental PA diminishing during adolescence and being replaced by sibling and peer PA (Duncan et al, 2007; Sallis et al, 2000). A recent study of 17 childhood cancer survivors aged 10 to 17 evaluated relations between family PA and child/adolescent cancer survivors’ PA (Norris, Moules, Pelletier, Culos-Reed, 2010). Survivors’ PA was related to maternal PA, but not father or sibling PA.…”
Section: Predictors Of Physical Activitymentioning
confidence: 99%
“…As children grow older, this relation becomes less consistent (Gustafson & Rhodes, 2006; Heitzler et al, 2006; Sallis et al, 2000), with the influence of parental PA diminishing during adolescence and being replaced by sibling and peer PA (Duncan et al, 2007; Sallis et al, 2000). A recent study of 17 childhood cancer survivors aged 10 to 17 evaluated relations between family PA and child/adolescent cancer survivors’ PA (Norris, Moules, Pelletier, Culos-Reed, 2010). Survivors’ PA was related to maternal PA, but not father or sibling PA.…”
Section: Predictors Of Physical Activitymentioning
confidence: 99%
“…Example questions include: “For a pupil who has returned to school during/after treatment for cancer how much would you expect that pupil to participate in PA (PE)?,” and “If extra PE were prescribed for a pupil returning to school during or after successful treatment for cancer, e.g. an additional 25 minutes of PE per day, could your school accommodate?” Several studies implemented the use of cross-sectional self-reported surveys (1619). The Godwin Leisure Time Exercise Questionnaire was used by several studies to evaluate the PA levels in pediatric oncology patients (16, 17, 20).…”
Section: Resultsmentioning
confidence: 99%
“…an additional 25 minutes of PE per day, could your school accommodate?” Several studies implemented the use of cross-sectional self-reported surveys (1619). The Godwin Leisure Time Exercise Questionnaire was used by several studies to evaluate the PA levels in pediatric oncology patients (16, 17, 20). The Pediatric Quality of Life Inventory Version 4.0 was used to measure the health-related quality of life (HRQL) (16).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A recent study (Norris et al 2010) reported a significant correlation between the PA levels of parents and those of child survivors.…”
Section: Practical Clinical Recommendationsmentioning
confidence: 96%